Business models to create customer loyalty and generate profitability : Groupon’s case - Silva, Marta Oliveira (2013)
Groupon is one of the fastest companies in the E-Commerce industry. Launched in 2008 in Chicago, Groupon is already present in 47 countries, 5 continents and more than 750 cities all over the world. The company works as an intermediary between consumers and local merchants by selling discounts online. The concept of Groupon is seen as an emerging marketing tool for local merchants and a new shopping experience for consumers. One of the main promises of Groupon is to enable customer loyalty and customer retention to merchants. However, merchants’ perception is that the customers that redeem the coupons do not come back and pay full price for the service/product provided. The main objective of this dissertation is for students and Professors to analyze two different loyalty dimensions: the customer loyalty towards local merchants and customer loyalty towards Groupon and to understand the importance of the role of loyalty in this case study. The dissertation is divided in to three main parts: the Case-Study (Literature Review, industry overview and Groupon’s analysis); the Market Research, performed in the context of Groupon Portugal, which contains the analysis on questionnaires and interviews performed to consumers and local merchants and, at last, the conclusions and future research comments and suggestions. Moreover, through this dissertation and teaching notes it is possible to retain some insights of an external perspective of the company, which represent an opportunity to improve some of the loyalty initiatives developed by local merchants and Groupon.